My grandfather's rojak - Lim-Leh, Emily 1971- (Scholastic Singapore, 2022)
"Guo's teacher gives his class a holiday assignment to do something different from what they are used to. Guo helps his grandfather at their family rojak stall every day, carrying out the same chores daily. What can he do that will be different, but still help his grandfather? Join Guo as he figures out a way to give the familiar a new twist!"-- Back cover
Scholastic picture book award shortlisted
Keywords: Ess- und Trinksitte; Streetfood; Singapur; Children's stories, Singaporean (English); Rojak; Bilderbuch